Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 02, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 02, 1930. The following month came the orders moving Hawley and his regiment north for the campaign in Virginia. Needless to say, Hawley rejoiced to go where it appeared that effective fighting might be done.
1 electronic record. Scanned newspaper article. 2 image scans. 1.34 MB (1,415,600 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 40.1 MB (42,150,376 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers